Analisis Ketidaksesuaian Praktik Murabahah Bil Wakalah dalam Perspektif Hukum Ekonomi Syariah (Studi pada LKMS Gapoktan Panampuang Prima) - Rufaidah Alaida Balqis; Fajrul Wadi (Lembaga Yasin AlSys, 2026)
The practice of murabahah bil wakalah contracts in Islamic microfinance institutions has been widely studied, but research specifically analyzing discrepancies in their implementation from the perspective of Sharia Economic Law in agribusiness-based Islamic microfinance institutions remains limited. This study aims to analyze the implementation of murabahah bil wakalah contracts and their compliance with the principles of Sharia Economic Law at LKMS-A Gapoktan Panampuang Prima. The study employed a qualitative approach with a case study design. The research informants consisted of the administrators of LKMS-A Gapoktan Panampuang Prima and financing customers selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation and were then analyzed using an interactive analysis model comprising data reduction, data presentation, and conclusion drawing. The results show that the implementation of murabahah bil wakalah contracts generally followed the applicable financing procedures, including financing applications, surveys, contract signing, fund disbursement, the purchase of goods by customers based on authorization (wakalah), and installment payments. However, several discrepancies were identified, including the use of financing funds for purposes inconsistent with the objectives of the contract, the limited understanding of some customers regarding the substance of the contract, and suboptimal supervision following fund disbursement. This study concludes that the implementation of murabahah bil wakalah contracts at LKMS-A Gapoktan Panampuang Prima has not fully complied with the principles of Sharia compliance. These findings contribute to the development of Sharia Economic Law studies on the implementation of murabahah bil wakalah contracts in Islamic microfinance institutions and provide practical implications for the institution to strengthen customer education and its financing supervision system.